Silent truth - Kenyon, Sherrilyn, 1965- (Paranormal Romance, 2010)
Bureau of American Defense agent Hunter Thornton-Payne is distracted from his long hunt for a ruthless assassin by the lovely Abby Blandon, who draws him into a dangerous conspiracy involving the government and an evil enterprise.